Cytoskeleton: signaling and cell regulation : a practical approach - Carraway, Kermit L (Oxford University Press, 2000)
This book provides descriptions of experimental methods in research on the cytoskeleton and its relationships to signaling and cell regulation. Thus, it bridges two active and fertile areas of research. The focus is directed particularly towards methods which take advantage of recent advances in molecular biology, microscopy and immunological assays. A second emphasis is on methods for understanding dynamic changes in cells. A third emphasis is on the formation and turnover of macromolecular and supramolecular complexes, which are so important in driving cell regulation and the behavior of cytoskeletal elements. A combination of practical advice and detailed protocols should make this book valuable for both novice and experienced workers in these burgeoning fields.
Practical approach series
Keywords: Cytoskeleton; cytologie, klinická cytologie; cytoskelet